CP-118 Does a structured protocol increase implementation of biologic therapy dose reduction among clinicians and patients? a pilot study. (25th February 2017) - Rose, E; Creamer, P; Jamal, MS
Abstract : Background: Biologic therapies (eg, tumour necrosis factor inhibitors (TNFi)) used in the management of inflammatory arthritis are associated with potential risks (including local reactions, infections and possible malignancy). Increasing RCT evidence suggests stable patients can dose reduce without increased disease activity and a previous patient engagement event explored patient perceptions of dose reduction. There are no clear guidelines or strategies reported in the literature to facilitate implementation in clinical practice. Purpose: For 2 years at the local NHS Trust, stable patients (out of the 460 patients on subcutaneous TNFi) were offered the opportunity to reduce their dose on an ad hoc basis with variable regimens. The purpose of this pilot study was to develop a structured programme for standardising dose reduction of subcutaneous TNFi therapy to support implementation among clinicians and patients. Material and methods: An inflammatory arthritis TNFi 5 step dose reduction programme was developed (30% interval extension for 3 steps, followed by a 60% extension, before stopping treatment), with a patient information and compliance record (informing of treatment escalation following a disease flare up). The programme was reviewed by a consultant rheumatologist and patient representative group, and presented to the clinical team, and treatment checklists were updated to include a prompt. Patients started on dose reduction schemes were recorded. Results: In the 2 years preceding the pilot, 27 patients attempted TNFi dose reduction (average rate of 1.1/month). In the first 6 months following introduction of the programme, an additional 42 patients (56% increase) were initiated on dose reduction schemes (average rate of 7/month). Of the 42 additional patients, 31 (74%) were initiated on the formal BTRIM programme and 11 (26%) were extended via an alternative schedule. Conclusion: The pilot showed that adopting a structured dose reduction programme increased implementation in clinical practice. It is unclear whether this was attributable to increased patient and/or clinician confidence or raised clinician awareness. Reasons for opting out were not assessed. Further work has been identified following the pilot, including potential gainshare discussions with commissioners and approval of a research grant to conduct a qualitative study assessing patient perceptions of biologic therapy dose reduction. References and/or acknowledgements: Rheumatology patient representative group, Local Trust. No conflict of interest